PENGGUNAAN MEDIA PEMBELAJARAN POSTER BERBASIS PENDEKATAN SAINTIFIK TERHADAP KEMAMPUAN KOGNITIF PESERTA DIDIK - Munirah, Munirah; Rosdiana; Hadmawati, Nurul (AULADUNA: Jurnal Pendidikan Dasar Islam, 2022)
AbstractThis study aimed to know the influence of using poster learning media based on the scientific approach to the students’ cognitive ability, especially lessons of Islamic education in the fifth-grade students of SDI Raulo district in Parigi, Gowa Regency. This research used ex post facto type. The population of this research was the students of SDI Raulo, consisting of 17 students. The research results indicated that: (1) the average score of using poster learning media in SDI Roulo was still in the medium category, with an achievement maximum 84 and a minimum 68, (2) the average score of students’ cognitive ability of Islamic education lessons for the fifth grade in SDI Raulo were in a medium category with achievement maximum 87 and minimum 76, and (3) there was an influence of using poster learning media to students’ cognitive ability in Islamic Education lessons. The teachers should use learning media such as posters to interest students in learning Islamic education lessons.